Welfare effects of fuel tax and feebate policies in the Japanese new car market - Tatsuya Abe (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This paper examines the efficiency and distributional effects of fuel tax and feebate policies in the automobile market. I employ a model in which households make two-stage decisions on car ownership and utilization, and I estimate model parameters by combining micro-level data from a household survey and macro-level aggregate data on the Japanese new car market from 2006 through 2013. Interestingly, several system changes in the Japanese feebate created rich variations in vehicle prices across vehicles and over time during the sample period. I use such exogenous variation to overcome the vehicle price endogeneity associated with demand estima- tion. Counterfactual analyses show that the Japanese feebate results in a significant increase in social welfare while augmenting environmental externalities. In particular, the rebound effect induced by the feebate cancels out approximately 7% of the reduction in CO2 emissions that would originally have been attained by the improvement in fuel economy. In addition, I find that the fuel tax at the current tax rate in Japan is 1.7 times less costly than the product tax, an alternative feebate scheme considered in the counterfactuals. I also find that there is no dif- ference in regressivity between the two policies in reducing negative environmental externalities by the same amount.
Keywords: D12; H23; L62; Q53; 330; Discrete-Continuous choice; Fuel tax; Feebate policy; Rebound effect; Decomposition; Distributional impact